2006
DOI: 10.1038/sj.ki.5001771
|View full text |Cite
|
Sign up to set email alerts
|

Response to ‘Mortality risk for patients receiving hemodiafiltration versus hemodialysis’

Abstract: The Nijmegen Biomedical Study is a population-based cross-sectional study conducted in the eastern part of the Netherlands. As part of the overall study, we provide reference values of estimated glomerular filtration rate (GFR) for this Caucasian population without expressed risk. Age-stratified, randomly selected inhabitants received a postal questionnaire on lifestyle and medical history. In a large subset of the responders, serum creatinine was measured. The GFR was then measured using the abbreviated Modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…This index is related to chronic in ammation in CKD patients due to metabolic changes in erythropoiesis mediated by cytokines such as IL-1, TNF-alpha, and IFN-gamma (17,18). Previous studies have shown that HDF is associated with the reduction of chronic in ammation by clearing larger molecules such as proin ammatory cytokines and other molecules, such as EPO (7,(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This index is related to chronic in ammation in CKD patients due to metabolic changes in erythropoiesis mediated by cytokines such as IL-1, TNF-alpha, and IFN-gamma (17,18). Previous studies have shown that HDF is associated with the reduction of chronic in ammation by clearing larger molecules such as proin ammatory cytokines and other molecules, such as EPO (7,(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…ALP hydrolyses inorganic phosphate, which is a potent endogenous inhibitor of the calci cation process, as well as being an important cardiovascular risk marker investigated in individuals with CKD, especially the elderly (30)(31)(32). CRP is one of the main markers of liver damage associated with CKD (7,33). In contrast to what was observed in this study, studies indicate a reduction in CRP with the conversion from HD to HDF (14,20,34).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the European Clinical Database (EuCliD) on 394 patients receiving OL‐HDF and 2170 receiving hemodialysis were examined 34 . Investigators demonstrated a 35.3% reduced risk of mortality associated with HD OL‐HDF (15–25 L/session) relative to hemodialysis 35 . The RISCAVID (RISchio CArdiovascolare nei pazienti afferenti all' Area Vasta In Dialisi) study examined data from 757 patients with ESKD and found that OL‐HDF (22–25 L/session of CV) resulted in higher cumulative survival than standard HD, even after model adjustments (RR for mortality: 0.78; p = 0.01) 36 .…”
Section: Evidence Base For Hdf: Observational Studiesmentioning
confidence: 99%
“… 34 Investigators demonstrated a 35.3% reduced risk of mortality associated with HD OL‐HDF (15–25 L/session) relative to hemodialysis. 35 The RISCAVID (RISchio CArdiovascolare nei pazienti afferenti all' Area Vasta In Dialisi) study examined data from 757 patients with ESKD and found that OL‐HDF (22–25 L/session of CV) resulted in higher cumulative survival than standard HD, even after model adjustments (RR for mortality: 0.78; p = 0.01). 36 In 2018, See and colleagues published data from the Australia and New Zealand Dialysis and Transplant (ANZDATA) Registry.…”
Section: Evidence Base For Hdf: Observational Studiesmentioning
confidence: 99%
“…Canaud et al ont montré à partir de l'étude observationnelle DOPPS que l' hémodiafiltration postdilution permettait de réduire la mortalité de 35% par rapport à l'hémodialyse conventionnelle à condition d'obtenir des volumes filtrés de plus de 15 litres(41). Quelques années plus tard, trois études prospectives randomisées comparant l' hémodiafiltration en ligne à l'hémodialyse, bien qu'ayant des résultats divergents suggéraient toutes que le traitement par hémodiafiltration postdilution était associé à une amélioration de la survie, à la condition d'obtenir des volumes convectifs élevés (cible plus de 23,1 l dans Estudio de Supervivencia de Hemodiafiltración Online [ESHOL])(42)(43)(44).…”
unclassified